Flexural modeling of the Manila Trench based on subduction dip: comparison of north-south subduction differences - Lu, Yunqian; Wang, Lijie; Peng, Yihui; Meng, Dajiang; Lin, Jiangnan (Frontiers in Marine Science, 2025)
The Manila Trench, representing relatively young (16–36 Ma) subducting slabs, has been flexurally modeled to assess its subduction morphology. This modeling enables predictions of subduction-related earthquake locations and provides critical insights into subduction dynamics. We utilized a lithospheric flexural model controlled by trench axis flexural wavelength (W0), initial subduction dip angle (β0), and elastic thickness (Te) to quantify variations in plate flexural bending along the Manila Trench. By correcting for the effects of high resolution sediment loads and removing residual short-wavelength features from observed water depths along 40 cross-trench profiles, we obtained key flexural parameters of the subducted oceanic crust. Our results show that the width of trench valley (X0) ranges from ca. 7 to 151 km, the bulge height (Wb) varies between 0.014 and 1.15 km, and the location of the shallowest point (Xb) is 25 to 201 km from the trench axis. The effective elastic thickness (Te) of the oceanic lithosphere ranges from 5 to 25 km, while the initial subduction dip angle (β0) is 0.1–9.8°, and the trench relief (W0) ranges from 0.3 to 2.6 km. The initial subduction dip angle exhibits significant variation along the trench, with an averaged β0 of 3.42° in the southern segment, 5.68° in the central segment, and less than 0.5° in the northern segment. These variations in flexural parameters at different segments are related to the nature of the subducting crust and the oblique subduction of the Philippine Plate. The sharp increase in the initial subduction dip angle in the central segment is associated with the presence of a slab window.